Ceramic tile with metallic luster and preparation method thereof
By combining ceramic body, surface glaze and metallic glaze in a specific ratio, and using materials with excellent chemical stability, the problem of insufficient gloss and stain resistance of ceramic tiles has been solved, achieving a metallic shimmering effect with high gloss and high stain resistance.
Patent Information
- Application Number
- CN202411585997.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Existing tiles lack sufficient gloss and three-dimensional effect on both sides, are not delicate and beautiful, and have poor stain resistance.
By using a specific ratio of ceramic body, surface glaze, metallic glaze and suspending agent, ceramic tiles with metallic luster are prepared through inkjet printing and firing processes. Metallic glaze is prepared using gold dry granules, platinum dry granules, transparent dry granules, flux protective glaze and suspending agent. Materials with excellent chemical stability and thermal conductivity, such as tantalum nitride, beryllium zirconate, niobium nitride and tetracarboxylated phthalocyanine vanadium, are combined to improve gloss and stain resistance.
The prepared ceramic tiles have a high gloss, delicate and beautiful metallic sheen, a three-dimensional effect with light and shadow, and a stain resistance level of 5.
Smart Images

Figure CN119118639B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic tiles, and in particular to a ceramic tile with metallic luster and a preparation method thereof. Background Art
[0002] In the field of modern home decoration, with the continuous changes in people's aesthetic concepts and the growing personalized needs, the decoration style shows a diversified development trend. In this process, metal plates, with their natural and unique texture and strong glossiness, have become a key element to improve the grade and quality of home decoration. The use of metal plates can not only make the home environment more modern and fashionable, but also create a unique artistic atmosphere, which is deeply loved by consumers.
[0003] However, metal plates also face some unavoidable problems during use. As metal plates are constantly in contact with oxygen in the air, a series of chemical reactions will occur over time, the most common of which is oxygen absorption corrosion. This phenomenon will not only seriously affect the appearance of the metal plate, causing it to lose its original luster and texture, but may also further affect its service life and even seriously affect its anti-fouling effect.
[0004] In summary, after extensive searching by the applicant, it is found that at least the existing ceramic tiles in this field have insufficient gloss and three-dimensional effect of the positive and negative surfaces, lack delicate and beautiful metallic glare, and have poor anti-fouling performance. Therefore, it is necessary to develop or improve a ceramic tile with metallic luster and a preparation method thereof. Summary of the invention
[0005] Based on this, in order to solve the problems that the existing ceramic tiles have insufficient gloss, three-dimensional effect of the positive and negative surfaces, no delicate and beautiful metal glare, and poor anti-fouling performance, the present invention provides a ceramic tile with metallic luster and a preparation method thereof. The specific technical scheme is as follows:
[0006] A ceramic tile with metallic luster, the raw materials for preparing the ceramic tile include a ceramic body, a glaze, ceramic ink and a metallic glaze;
[0007] The raw materials for preparing the metal glaze include gold dry particles, platinum dry particles, transparent dry particles, fluxing protective glaze and suspending agent;
[0008] The raw materials for preparing the gold dry particles include silicon oxide, aluminum oxide, titanium oxide, calcium oxide, cobalt oxide, tantalum nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium;
[0009] The raw materials for preparing the platinum dry particles include silicon oxide, aluminum oxide, iron oxide, titanium oxide, calcium oxide, cobalt oxide, niobium nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium;
[0010] The raw materials for preparing the suspension agent include carboxymethyl cellulose, alpha-hydroxy-omega-carboxyl polyethylene glycol, N-benzanilide-4,4'-dicarboxylic acid, urea-modified polyurethane solution, aluminum oxide and water.
[0011] Furthermore, the method for preparing the ceramic body comprises the following steps:
[0012] By mass, 65-75 parts of silicon oxide, 14-20 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-6 parts of calcium oxide, 1-4 parts of magnesium oxide, 3-7 parts of potassium oxide and 2-5 parts of sodium oxide are mixed evenly, and then pressed to obtain the ceramic body.
[0013] Furthermore, the preparation method of the transparent dry particles comprises the following steps:
[0014] By mass, 50-60 parts of silicon oxide, 15-25 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-8 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-5 parts of sodium oxide, 3-7 parts of zinc oxide, 0-1 part of lead oxide, 1-4 parts of strontium oxide and 4-8 parts of barium oxide are uniformly mixed, and then granulated to obtain the transparent dry particles;
[0015] The particle grading of the transparent dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 20 to 30%, 150 mesh to 200 mesh: 35 to 50%, 200 mesh to 250 mesh: 25 to 35%, and above 250 mesh: 3 to 10%.
[0016] Furthermore, the preparation method of the gold dry particles comprises the following steps:
[0017] By mass, 30-35 parts of silicon oxide, 8-15 parts of aluminum oxide, 45-60 parts of titanium oxide, 3-7 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of tantalum nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the gold dry particles;
[0018] The particle size distribution of the gold dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%;
[0019] The preparation method of the platinum dry particles comprises the following steps:
[0020] By mass, 30-40 parts of silicon oxide, 8-15 parts of aluminum oxide, 40-60 parts of iron oxide, 3-8 parts of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of niobium nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the platinum dry particles;
[0021] The particle size distribution of the platinum dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%.
[0022] Furthermore, the preparation method of the flux protective glaze comprises the following steps:
[0023] By mass, 40 to 50 parts of silicon oxide, 8 to 18 parts of aluminum oxide, 0 to 1 part of iron oxide, 0 to 1 part of titanium oxide, 1 to 3 parts of calcium oxide, 2 to 5 parts of magnesium oxide, 2 to 5 parts of potassium oxide, 1 to 3 parts of sodium oxide, 5 to 8 parts of zinc oxide and 22 to 30 parts of barium oxide are uniformly mixed to obtain the flux protective glaze.
[0024] Furthermore, the preparation method of the glaze comprises the following steps:
[0025] By mass, 60-70 parts of silicon oxide, 18-27 parts of aluminum oxide, 0-1 part of iron oxide, 0-0.5 part of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-3 parts of sodium oxide, 0-0.5 part of zinc oxide and 0-1 part of barium oxide are uniformly mixed to obtain the glaze.
[0026] Furthermore, the preparation method of the suspension comprises the following steps:
[0027] 15-25 parts of carboxymethyl cellulose and 5-15 parts of urea-modified polyurethane solution are added to the 35-48 parts of water by mass, stirred evenly, and then 5-15 parts of α-hydroxy-ω-carboxyl polyethylene glycol, 5-15 parts of N-benzanilide-4,4'-dicarboxylic acid and 5-15 parts of aluminum oxide are added, and ultrasonicated for 8-12 minutes to obtain the suspending agent.
[0028] Furthermore, the preparation method of the metal glaze comprises the following steps:
[0029] The gold dry particles, platinum dry particles, transparent dry particles, flux protection glaze and suspending agent are mixed evenly to obtain the metal glaze;
[0030] The mass ratio of the gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent is 7-11:7-11:30-40:10-20:90-110.
[0031] The technical solution also provides a method for preparing ceramic tiles with metallic luster, which comprises the following steps:
[0032] The ceramic body is dried at 180-200°C for 30-40 minutes, and the moisture content is controlled at 0.3%-0.9%. The surface of the ceramic body is then glazed with a bell jar. A preset pattern file is then inkjet printed on the glazed ceramic body using ceramic ink. The metal glaze is then glazed with a bell jar. The ceramic body is then fired in a kiln and then polished, edged, graded, and packaged into a warehouse to obtain the ceramic tile with a metallic luster.
[0033] Furthermore, the maximum sintering temperature is 1180-1210°C;
[0034] The specific gravity of the glaze is 1.88-1.90 g / cm 3 The glaze amount of the top glaze is 400-500 g / m 2 ;
[0035] The specific gravity of the metal glaze is 1.12-1.15 g / cm 3 The glazing amount of the metal glaze is 400-500 g / m 2 ;
[0036] The polishing grinding blocks are arranged as 2 to 5 groups of 180 mesh grinding brushes, and / or 3 to 8 groups of 600 mesh elastic grinding blocks, and / or 3 to 8 groups of 800 mesh elastic grinding blocks, and / or 2 to 7 groups of 2000 mesh elastic grinding blocks, and / or 7 to 13 groups of 320 mesh fiber grinding blocks.
[0037] The tiles obtained by the above technical solution not only have high gloss and delicate and beautiful metallic glare, but also have a three-dimensional effect of yin and yang surfaces, and its anti-fouling level is as high as level 5. Specifically, since tantalum nitride has excellent chemical stability and thermal conductivity, beryllium zirconate has excellent corrosion resistance and good thermal conductivity, niobium nitride has excellent corrosion resistance, thermal stability and thermal conductivity, and tetracarboxyphthalocyanine vanadium has excellent chemical stability and heat resistance, α-hydroxy-ω-carboxy polyethylene glycol has good stability and abundant reactive groups, and N-benzanilide-4,4'-dicarboxylic acid has multiple functional groups, the metal glaze prepared by gold dry particles containing tantalum nitride, beryllium zirconate and tetracarboxyphthalocyanine vanadium, platinum dry particles containing niobium nitride, beryllium zirconate and tetracarboxyphthalocyanine vanadium, and a suspension containing α-hydroxy-ω-carboxy polyethylene glycol and N-benzanilide-4,4'-dicarboxylic acid can make the final ceramic tile have high-gloss, delicate and beautiful metallic glare, and have a three-dimensional effect of yin and yang surfaces, and its anti-fouling level is as high as level 5. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 is a picture of the tiles of Example 1;
[0039] Figure 2 is a picture of the tiles of Example 2;
[0040] Figure 3 is a picture of tiles of Example 3;
[0041] Figure 4 This is a picture of the tiles in Comparative Example 1;
[0042] Figure 5 This is a picture of the tiles in Comparative Example 2;
[0043] Figure 6 This is a picture of the tiles in Comparative Example 3;
[0044] Figure 7 This is a picture of the tiles of Example 4. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.
[0046] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0047] A ceramic tile with metallic luster in one embodiment of the present invention, the raw materials for preparing the ceramic tile include a ceramic body, a glaze, ceramic ink and a metallic glaze;
[0048] The raw materials for preparing the metal glaze include gold dry particles, platinum dry particles, transparent dry particles, fluxing protective glaze and suspending agent;
[0049] The raw materials for preparing the gold dry particles include silicon oxide, aluminum oxide, titanium oxide, calcium oxide, cobalt oxide, tantalum nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium;
[0050] The raw materials for preparing the platinum dry particles include silicon oxide, aluminum oxide, iron oxide, titanium oxide, calcium oxide, cobalt oxide, niobium nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium;
[0051] The raw materials for preparing the suspension agent include carboxymethyl cellulose, alpha-hydroxy-omega-carboxyl polyethylene glycol, N-benzanilide-4,4'-dicarboxylic acid, urea-modified polyurethane solution, aluminum oxide and water.
[0052] In one embodiment, the method for preparing the ceramic body comprises the following steps:
[0053] By mass, 65-75 parts of silicon oxide, 14-20 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-6 parts of calcium oxide, 1-4 parts of magnesium oxide, 3-7 parts of potassium oxide and 2-5 parts of sodium oxide are mixed evenly, and then pressed to obtain the ceramic body.
[0054] In one embodiment, the method for preparing the transparent dry particles comprises the following steps:
[0055] By mass, 50-60 parts of silicon oxide, 15-25 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-8 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-5 parts of sodium oxide, 3-7 parts of zinc oxide, 0-1 part of lead oxide, 1-4 parts of strontium oxide and 4-8 parts of barium oxide are uniformly mixed, and then granulated to obtain the transparent dry particles;
[0056] The particle grading of the transparent dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 20 to 30%, 150 mesh to 200 mesh: 35 to 50%, 200 mesh to 250 mesh: 25 to 35%, and above 250 mesh: 3 to 10%.
[0057] In one embodiment, the method for preparing the gold dry particles comprises the following steps:
[0058] By mass, 30-35 parts of silicon oxide, 8-15 parts of aluminum oxide, 45-60 parts of titanium oxide, 3-7 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of tantalum nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the gold dry particles;
[0059] The particle size distribution of the gold dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%;
[0060] The preparation method of the platinum dry particles comprises the following steps:
[0061] By mass, 30-40 parts of silicon oxide, 8-15 parts of aluminum oxide, 40-60 parts of iron oxide, 3-8 parts of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of niobium nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the platinum dry particles;
[0062] The particle size distribution of the platinum dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%.
[0063] In one embodiment, the method for preparing the flux protective glaze comprises the following steps:
[0064] By mass, 40 to 50 parts of silicon oxide, 8 to 18 parts of aluminum oxide, 0 to 1 part of iron oxide, 0 to 1 part of titanium oxide, 1 to 3 parts of calcium oxide, 2 to 5 parts of magnesium oxide, 2 to 5 parts of potassium oxide, 1 to 3 parts of sodium oxide, 5 to 8 parts of zinc oxide and 22 to 30 parts of barium oxide are uniformly mixed to obtain the flux protective glaze.
[0065] In one embodiment, the method for preparing the glaze comprises the following steps:
[0066] By mass, 60-70 parts of silicon oxide, 18-27 parts of aluminum oxide, 0-1 part of iron oxide, 0-0.5 part of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-3 parts of sodium oxide, 0-0.5 part of zinc oxide and 0-1 part of barium oxide are uniformly mixed to obtain the glaze.
[0067] In one embodiment, the method for preparing the suspension comprises the following steps:
[0068] 15-25 parts of carboxymethyl cellulose and 5-15 parts of urea-modified polyurethane solution are added to the 35-48 parts of water by mass, stirred evenly, and then 5-15 parts of α-hydroxy-ω-carboxyl polyethylene glycol, 5-15 parts of N-benzanilide-4,4'-dicarboxylic acid and 5-15 parts of aluminum oxide are added, and ultrasonicated for 8-12 minutes to obtain the suspending agent.
[0069] In one embodiment, the method for preparing the metal glaze comprises the following steps:
[0070] The gold dry particles, platinum dry particles, transparent dry particles, flux protection glaze and suspending agent are mixed evenly to obtain the metal glaze;
[0071] The mass ratio of the gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent is 7-11:7-11:30-40:10-20:90-110.
[0072] In one embodiment, the technical solution provides a method for preparing a ceramic tile with metallic luster, which comprises the following steps:
[0073] The ceramic body is dried at 180-200°C for 30-40 minutes, and the moisture content is controlled at 0.3%-0.9%. The surface of the ceramic body is then glazed with a bell jar. A preset pattern file is then inkjet printed on the glazed ceramic body using ceramic ink. The metal glaze is then glazed with a bell jar. The ceramic body is then fired in a kiln and then polished, edged, graded, and packaged into a warehouse to obtain the ceramic tile with a metallic luster.
[0074] In one embodiment, the maximum sintering temperature is 1180-1210°C;
[0075] The specific gravity of the glaze is 1.88-1.90 g / cm 3 The glaze amount of the top glaze is 400-500 g / m 2 ;
[0076] The specific gravity of the metal glaze is 1.12-1.15 g / cm 3 The glazing amount of the metal glaze is 400-500 g / m 2 ;
[0077] The polishing grinding blocks are arranged as 2 to 5 groups of 180 mesh grinding brushes, and / or 3 to 8 groups of 600 mesh elastic grinding blocks, and / or 3 to 8 groups of 800 mesh elastic grinding blocks, and / or 2 to 7 groups of 2000 mesh elastic grinding blocks, and / or 7 to 13 groups of 320 mesh fiber grinding blocks.
[0078] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0079] Embodiment 1:
[0080] Preparation of a ceramic body: 67.23 parts of silicon oxide, 17.18 parts of aluminum oxide, 0.11 parts of iron oxide, 0.05 parts of titanium oxide, 4.64 parts of calcium oxide, 2.32 parts of magnesium oxide, 5.48 parts of potassium oxide and 3 parts of sodium oxide were mixed uniformly by mass, and then pressed to obtain a ceramic body;
[0081] Preparation of the glaze: 65.71 parts of silicon oxide, 23.94 parts of aluminum oxide, 0.16 parts of iron oxide, 0.07 parts of titanium oxide, 2.78 parts of calcium oxide, 0.96 parts of magnesium oxide, 3.5 parts of potassium oxide, 1.95 parts of sodium oxide, 0.03 parts of zinc oxide and 0.65 parts of barium oxide were mixed uniformly by mass to obtain the glaze;
[0082] Preparation of transparent dry granules: 53.73 parts of silicon oxide, 19.59 parts of aluminum oxide, 0.18 parts of iron oxide, 0.18 parts of titanium oxide, 5.18 parts of calcium oxide, 1.56 parts of magnesium oxide, 3.69 parts of potassium oxide, 2.58 parts of sodium oxide, 4.23 parts of zinc oxide, 0.34 parts of lead oxide, 2.5 parts of strontium oxide and 6.05 parts of barium oxide are mixed uniformly by mass, and then granulated to obtain transparent dry granules, wherein the particle gradation of the transparent dry granules is: below 120 mesh: none, 120 mesh to 150 mesh: 25%, 150 mesh to 200 mesh: 40%, 200 mesh to 250 mesh: 30%, and above 250 mesh: 5%;
[0083] Preparation of dry gold particles: 30.6 parts of silicon oxide, 12.3 parts of aluminum oxide, 50.4 parts of titanium oxide, 5.4 parts of calcium oxide, 1.3 parts of cobalt oxide, 5 parts of tantalum nitride, 5 parts of beryllium zirconate and 10 parts of tetracarboxyl phthalocyanine vanadium are mixed uniformly by mass, and then granulated to obtain dry gold particles, wherein the particle size distribution of the dry gold particles is: below 120 mesh: none, 120 mesh to 150 mesh: 60%, 150 mesh to 200 mesh: 25%, 200 mesh to 250 mesh: 10%, and above 250 mesh: 5%;
[0084] Preparation of platinum dry particles: 36.7 parts of silicon oxide, 8.8 parts of aluminum oxide, 48.6 parts of iron oxide, 6 parts of titanium oxide, 2.3 parts of calcium oxide, 1.6 parts of cobalt oxide, 5 parts of niobium nitride, 5 parts of beryllium zirconate and 10 parts of tetracarboxyl phthalocyanine vanadium are mixed uniformly by mass, and then granulated to obtain platinum dry particles, wherein the particle size distribution of the platinum dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 60%, 150 mesh to 200 mesh: 25%, 200 mesh to 250 mesh: 10%, and above 250 mesh: 5%;
[0085] Preparation of flux protective glaze: 45.17 parts of silicon oxide, 12.65 parts of aluminum oxide, 0.05 parts of iron oxide, 0.08 parts of titanium oxide, 1.62 parts of calcium oxide, 3.32 parts of magnesium oxide, 3.17 parts of potassium oxide, 1.96 parts of sodium oxide, 6.71 parts of zinc oxide and 25.27 parts of barium oxide are mixed uniformly by mass to obtain flux protective glaze;
[0086] Preparation of the suspension: Add 20 parts of carboxymethyl cellulose and 10 parts of urea-modified polyurethane solution to the 43 parts of water by mass, stir evenly, then add 10 parts of α-hydroxy-ω-carboxyl polyethylene glycol, 10 parts of N-benzanilide-4,4'-dicarboxylic acid and 10 parts of aluminum oxide, and ultrasonicate for 10 minutes to obtain a suspension;
[0087] Preparation of metallic glaze: the gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent are uniformly mixed to obtain metallic glaze, wherein the mass ratio of the gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent is 11:7:35:15:100;
[0088] Preparation of ceramic tiles: The ceramic body is dried at 190°C for 35 minutes, the moisture content is controlled at 0.6%, and then the surface of the ceramic body is coated with a bell jar, and then the ceramic ink is used to inkjet print the preset pattern file on the ceramic body coated with the surface glaze, and then the metal glaze is coated with the bell jar, and then it is fired in the kiln, and then polished, edged, graded and packaged into the warehouse to obtain ceramic tiles with metallic luster, wherein the highest firing temperature is 1205°C, and the specific gravity of the surface glaze is 1.89g / cm 3 The glaze amount of the top glaze is 450g / m 2 , the specific gravity of metal glaze is 1.13g / cm 3 The glaze weight of the metal glaze is 450g / m 2 The polishing abrasive blocks are arranged as 3 groups of 180-mesh grinding brushes, 5 groups of 600-mesh elastic abrasive blocks, 5 groups of 800-mesh elastic abrasive blocks, 4 groups of 2000-mesh elastic abrasive blocks, and 10 groups of 320-mesh fiber abrasive blocks. The elastic abrasive blocks of 600-mesh and 800-mesh have a pressure of 2 kg, and the other abrasive blocks have no pressure. The polishing glossiness is 35°.
[0089] Embodiment 2:
[0090] The other parts are the same as those in Example 1, except that the platinum dry particles are prepared as follows: 36.7 parts of silicon oxide, 8.8 parts of aluminum oxide, 48.6 parts of iron oxide, 6 parts of titanium oxide, 2.3 parts of calcium oxide, 1.6 parts of cobalt oxide, 5 parts of niobium nitride, 5 parts of beryllium zirconate and 15 parts of tetracarboxyphthalocyanine vanadium are uniformly mixed, and then granulated to obtain platinum dry particles. The mass ratio of gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent is 7:11:35:15:100.
[0091] Embodiment 3:
[0092] The other parts are the same as Example 1, except that the preparation of the gold dry particles is as follows: 30.6 parts of silicon oxide, 12.3 parts of aluminum oxide, 50.4 parts of titanium oxide, 5.4 parts of calcium oxide, 1.3 parts of cobalt oxide, 5 parts of tantalum nitride, 5 parts of beryllium zirconate and 5 parts of tetracarboxyphthalocyanine vanadium are uniformly mixed, and then granulated to obtain gold dry particles, and the mass ratio of gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agent is 9:9:35:15:100.
[0093] Comparative Example 1:
[0094] The other parts are the same as those in Example 1, except that the preparation part of the gold dry particles does not contain tantalum nitride, beryllium zirconate and tetracarboxyphthalocyanine vanadium.
[0095] Comparative Example 2:
[0096] The other parts are the same as those in Example 1, except that the preparation part of the platinum dry particles does not contain niobium nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium.
[0097] Comparative Example 3:
[0098] The other parts are the same as Example 1, except that the particle gradation of gold dry particles is: below 60 mesh: none, 60 mesh to 80 mesh: 30%, 80 mesh to 100 mesh: 35%, 100 mesh to 120 mesh: 30%, and above 120 mesh: 5%; the particle gradation of platinum dry particles is: below 60 mesh: none, 60 mesh to 80 mesh: 35%, 80 mesh to 100 mesh: 25%, 100 mesh to 120 mesh: 35%, and above 120 mesh: 5%; the polishing abrasive blocks are arranged as 3 groups of 400 mesh grinding brushes, 8 groups of 800 mesh elastic abrasive blocks, and 5 groups of 240 mesh fiber abrasive blocks, among which the elastic abrasive blocks of 800 mesh have a pressure of 2 kg, and the other abrasive blocks are not pressurized, and the polishing gloss is 35°.
[0099] Comparative Example 4:
[0100] The other parts are the same as Example 1, except that the suspension agent is prepared as follows: 20 parts of carboxymethyl cellulose and 10 parts of urea-modified polyurethane solution are added to the 43 parts of water by mass, stirred evenly, and then 10 parts of aluminum oxide are added, and ultrasonicated for 10 minutes to obtain the suspension agent.
[0101] The ceramic tiles obtained from Examples 1 to 3 and Comparative Examples 1 to 4 were subjected to performance tests, and the test results are shown in Table 1.
[0102] The particle gradation test method of the present invention is to measure the percentage of particle contents of materials that are left after passing through sieves with mesh sizes from low to high.
[0103] Table 1:
[0104]
[0105] As can be seen from Table 1, the ceramic tiles of Examples 1 to 3 are prepared from raw materials containing gold dry particles, platinum dry particles, transparent dry particles, flux protective glaze and suspending agents. The raw materials for preparing the gold dry particles include silicon oxide, aluminum oxide, titanium oxide, calcium oxide, cobalt oxide, tantalum nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium. The raw materials for preparing the platinum dry particles include silicon oxide, aluminum oxide, iron oxide, titanium oxide, calcium oxide, cobalt oxide, niobium nitride, beryllium zirconate and tetracarboxyl phthalocyanine vanadium. The raw materials for preparing the suspending agent include carboxymethyl cellulose, α-hydroxy-ω-carboxyl polyethylene glycol, N-benzanilide-4,4'-dicarboxylic acid, urea-modified polyurethane solution, aluminum oxide and water. The obtained ceramic tiles not only have high gloss and delicate and beautiful metallic glare, but also have a three-dimensional effect of yin and yang surfaces, and their anti-fouling grade is as high as level 5. Specifically, since tantalum nitride has excellent chemical stability and thermal conductivity, beryllium zirconate has excellent corrosion resistance and good thermal conductivity, niobium nitride has excellent corrosion resistance, thermal stability and thermal conductivity, and tetracarboxyphthalocyanine vanadium has excellent chemical stability and heat resistance, α-hydroxy-ω-carboxy polyethylene glycol has good stability and abundant reactive groups, and N-benzanilide-4,4'-dicarboxylic acid has multiple functional groups, the metal glaze prepared by gold dry particles containing tantalum nitride, beryllium zirconate and tetracarboxyphthalocyanine vanadium, platinum dry particles containing niobium nitride, beryllium zirconate and tetracarboxyphthalocyanine vanadium, and a suspension containing α-hydroxy-ω-carboxy polyethylene glycol and N-benzanilide-4,4'-dicarboxylic acid can make the final ceramic tile have high-gloss, delicate and beautiful metallic glare, and have a three-dimensional effect of yin and yang surfaces, and its anti-fouling level is as high as level 5.
[0106] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0107] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A ceramic tile with metallic luster, characterized in that: The raw materials for its preparation include ceramic body, glaze, ceramic ink and metal glaze; The raw materials for preparing the metal glaze include gold dry particles, platinum dry particles, transparent dry particles, flux protection glaze and suspending agent, and the gold dry particles, platinum dry particles, transparent dry particles, flux protection glaze and suspending agent are uniformly mixed in a mass ratio of 7-11:7-11:30-40:10-20:90-110 to obtain the metal glaze; The preparation method of the gold dry particles comprises the following steps: By mass, 30-35 parts of silicon oxide, 8-15 parts of aluminum oxide, 45-60 parts of titanium oxide, 3-7 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of tantalum nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the gold dry particles; The particle size distribution of the gold dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%; The preparation method of the platinum dry particles comprises the following steps: By mass, 30-40 parts of silicon oxide, 8-15 parts of aluminum oxide, 40-60 parts of iron oxide, 3-8 parts of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of cobalt oxide, 3-7 parts of niobium nitride, 3-7 parts of beryllium zirconate and 5-15 parts of tetracarboxyl phthalocyanine vanadium are uniformly mixed, and then granulated to obtain the platinum dry particles; The particle size distribution of the platinum dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 50 to 70%, 150 mesh to 200 mesh: 20 to 30%, 200 mesh to 250 mesh: 5 to 15%, and above 250 mesh: 3 to 10%; The preparation method of the suspension comprises the following steps: By mass, 15-25 parts of carboxymethyl cellulose and 5-15 parts of urea-modified polyurethane solution are added to 35-48 parts of water, stirred evenly, and then 5-15 parts of α-hydroxy-ω-carboxyl polyethylene glycol, 5-15 parts of N-benzanilide-4,4'-dicarboxylic acid and 5-15 parts of aluminum oxide are added, and ultrasonicated for 8-12 minutes to obtain the suspension.
2. The ceramic tile according to claim 1, characterized in that: The method for preparing the ceramic body comprises the following steps: By mass, 65-75 parts of silicon oxide, 14-20 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-6 parts of calcium oxide, 1-4 parts of magnesium oxide, 3-7 parts of potassium oxide and 2-5 parts of sodium oxide are mixed evenly, and then pressed to obtain the ceramic body.
3. The tile according to claim 1, characterized in that: The preparation method of the transparent dry particles comprises the following steps: By mass, 50-60 parts of silicon oxide, 15-25 parts of aluminum oxide, 0-1 part of iron oxide, 0-1 part of titanium oxide, 3-8 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-5 parts of sodium oxide, 3-7 parts of zinc oxide, 0-1 part of lead oxide, 1-4 parts of strontium oxide and 4-8 parts of barium oxide are uniformly mixed, and then granulated to obtain the transparent dry particles; The particle grading of the transparent dry particles is: below 120 mesh: none, 120 mesh to 150 mesh: 20 to 30%, 150 mesh to 200 mesh: 35 to 50%, 200 mesh to 250 mesh: 25 to 35%, and above 250 mesh: 3 to 10%.
4. The ceramic tile according to claim 1, characterized in that: The preparation method of the flux protective glaze comprises the following steps: By mass, 40 to 50 parts of silicon oxide, 8 to 18 parts of aluminum oxide, 0 to 1 part of iron oxide, 0 to 1 part of titanium oxide, 1 to 3 parts of calcium oxide, 2 to 5 parts of magnesium oxide, 2 to 5 parts of potassium oxide, 1 to 3 parts of sodium oxide, 5 to 8 parts of zinc oxide and 22 to 30 parts of barium oxide are uniformly mixed to obtain the flux protective glaze.
5. The ceramic tile according to claim 1, characterized in that: The preparation method of the glaze comprises the following steps: By mass, 60-70 parts of silicon oxide, 18-27 parts of aluminum oxide, 0-1 part of iron oxide, 0-0.5 part of titanium oxide, 1-4 parts of calcium oxide, 0.5-2 parts of magnesium oxide, 2-5 parts of potassium oxide, 1-3 parts of sodium oxide, 0-0.5 part of zinc oxide and 0-1 part of barium oxide are uniformly mixed to obtain the glaze.
6. A method for preparing a ceramic tile having a metallic luster, characterized in that: The preparation method is used to prepare the ceramic tile with metallic luster as claimed in claim 1, and comprises the following steps: The ceramic body is dried at 180-200°C for 30-40 minutes, and the moisture content is controlled at 0.3%-0.9%. The surface of the ceramic body is then glazed with a bell jar. A preset pattern file is then inkjet printed on the glazed ceramic body using ceramic ink. The metal glaze is then glazed with a bell jar. The ceramic body is then fired in a kiln and then polished, edged, graded, and packaged into a warehouse to obtain the ceramic tile with a metallic luster.
7. The preparation method according to claim 6, characterized in that: The maximum firing temperature is 1180~1210℃; The specific gravity of the glaze is 1.88-1.90 g / cm 3 The glaze amount of the top glaze is 400-500 g / m 2 ; The specific gravity of the metal glaze is 1.12-1.15 g / cm 3 The glazing amount of the metal glaze is 400-500 g / m 2 ; The polishing grinding blocks are arranged as 2 to 5 groups of 180 mesh grinding brushes, and / or 3 to 8 groups of 600 mesh elastic grinding blocks, and / or 3 to 8 groups of 800 mesh elastic grinding blocks, and / or 2 to 7 groups of 2000 mesh elastic grinding blocks, and / or 7 to 13 groups of 320 mesh fiber grinding blocks.
Citation Information
Patent Citations
Metal tile and preparation method thereof
CN109456048A
Metal dry granular glaze, metallic luster ceramic tile and preparation method of metallic luster ceramic tile
CN111847877A
Cited By
Charge localization platinum / gold dry pellets, tiles, and methods of making the same
CN120736798B